Analisa Dan Perancangan Sistem Informasi PPDB Online Berbasis Website Menggunakan Metode Waterfall Di SMK Gema Bangsa - Haqun Baitika; Yayah Zakiyah; Alfi Ardhiansyah; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Based on the analysis carried out, the manual admissions system at Gema Bangsa Vocational School experiences several obstacles including frequent human errors in the calculation process, writing and recording student names on student admission reports, requiring a long time in searching for data, delays in information and storage of evidence of student acceptance that is less effective. From the various kinds of problems above, the author made a study entitled "ANALYSIS AND DESIGN OF WEBSITE-BASED ONLINE PPDB INFORMATION SYSTEM USING THE WATERFALL METHOD IN GEMA BANGSA VOCATIONAL SCHOOL". In this study, researchers built a web-based application which is expected to make it easier for students to register anywhere and anytime. Coupled with this online PPDB feature to make it easier for new students to convey information more effectively.